PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT. SUMBER ALFARIA TRIJAYA TBK. BRANCH BOGOR - Nur Fadilah Nilam Cahya; Ading Sunarto (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of Reward and Punishment on Employee Performance both partially and simultaneously at PT. Sumber Alfaria Trijaya Tbk. Bogor Branch. This research method uses quantitative methods. The collection methods used are primary data and secondary data.this research used the Slovin Technique, namely 85 respondents. The analysis techniques used were validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test and hypothesis testing. Partially testing the hypothesis for the Reward variable (X1) obtained a calculated t value > t table (7.543 > 1.9893) and a significance value of 0.000 < 0.05. This means that Reward (X1) has a significant effect on Employee Performance (Y). Partially testing the hypothesis for the Punishment variable (X2) obtained a calculated t value > t table (3.492 > 1.9893) and a significance value of 0.001 < 0.05. This means that Punishment (X2) has a significant effect on Employee Performance (Y). Simultaneous hypothesis testing obtained fcount > ftable (190.815 > 3.11) and a significant value of 0.000 < 0.05. So it can be concluded that Reward (X1) and Punishment (X2) simultaneously have a significant effect on Employee Performance (Y). The determination obtained by the Adjusted R Square is 0.823, meaning that the Reward and Punishment variables together have an influence contribution of 82,3% on employee performance. Meanwhile, the remaining 17,7% was influenced by other factors not examined in this study